Pulsation Calculation of Chemical Transformation Products during Gas-Impulse Regeneration of Hole Filters - V. V. Ivashechkin; G. K. Dobrian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper considers a mathematical model of pulsation of gas explosion products in the operational chamber during gas-impulse regeneration of water well filters. Second-order differential equation with constant coefficients has been derived. A special calculation program has been developed to solve the equation. The paper proposes analytical method for determination of maximum hydraulic flow rate. In order to increase efficiency of regeneration improved technological treatment schemes are given in the paper.